Individual and Overall Analysis on Indonesian Stock Funds Market Timing and Selectivity - Amsal Irmalis; Muzakir Muzakir (universitas teuku umar, 2018)
This study investigates Timing and Selection ability of managers in Indonesia Funds Industry.The one month stock funds net asset value, Indonesian Treasury-Bill (3-Months) and Market rerturn of Indonesia Stock Exchange covering from 2010-2014 is used on this research. We apply Treynor-Mazuy Equation to test the hypothesis. This investigation exhibit the timing the capital market ability as well as selectivity possess by managers both individuall as well as overall point of view. The reult shows that, individual analysis on the funds proves that the almost all of the managers only have slight of ability. Only three of the assets exhibit affirmative and statistically substantial alpha and none of them display confident timing skill. Breakdown of overall funds endorses that managers show a weak selectivity and timing expertise. Keywords: Treynor-Mazuy, |Stock Funds, Timing and Selectivity Skill